Kontribusi Pemikiran M. M. A’zami, Yusuf Al-Qaradhawi, dan Khaled Abou El Fadl Dalam Hermeneutika Hadist - Indhra Musthofa; Husnul Khotimah (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
The Thought Contribution of M. M. A'zami, Yusuf Al-Qaradhawi, and Khaled Abou El Fadl in Hadith HermeneuticsAfter the death of Rosululloh SAW, the debate on the legitimacy of hadith as a source of Islamic law seems to have no end. In fact, the trend in this regard leads to an increasingly high debate regarding the legitimacy and authenticity of hadiths, this does not occur among Muslim hadith scholars, but also among non-Muslim western orientalists who are the focus of attention of hadith studies. The three intellectual figures who have arguments in advancing the authenticity of hadith. Therefore, this article analyzes the thoughts of three modern Muslim scholars regarding hadith, which occupies a central position as the second source of law in Islam. The study is focused on the thoughts offered by Muhammad Mustafa A'zami, Yusuf al-Qaradhawi, and Khaled Abou el Fadhl. This article uses the library research method and methodology of hadith criticism by referring to various written sources that are relevant to the focus of this study, using historical theory which contains hermeneutic analysis, then the study functions when comparing the three figures. Therefore, in this case, several things will be discussed regarding the various theories, arguments, and methodologies offered by these Muslim scholars to refute the theories developed by outsiders. First, with his historical-philological approach and his refutation of orientalism theories, Azami concludes that hadith is authentic, not as alleged by orientalists. Second, al-Qaradawi with his thoughts on the position of the sunnah ghairu tasyri'iyah, concluded that the sunnah ghairu tasyri'iyah has no legal consequences. Third, Abou El Fadl with his offer of authoritative reading of hadith through negotiating hermeneutics, finds that the interpretation of religious texts must pay attention to three interrelated components, namely the text-author-reader. The findings of this article are that there are examples of hadith analysis using the methodology of hadith criticism, here the author conducts analysis with arguments built from common link theory and projecting back.